Teachers Can Change Teacher Education by Influencing State Approval and National Accreditation - National Education Association, Washington, DC. Div. of Instruction and Professional Development; National Education Association, Washington, DC. Div. of Instruction and Professional Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This booklet provides members of the National Education Association (NEA) with background information about accreditation and certification so that they can take appropriate action to change teacher education. Part one presents an overview of accreditation and certification in teacher education. Section one of this part contains information on the purpose of accreditation, while sections two, three, and four discuss state approval, regional accreditation, and national accreditation. Interrelationships among accrediting associations are discussed in section five. Finally, the NEA position on self-governance is presented in section six. Appended in this first part is a list of licensure and accreditation boards for selected professions. Part two contains guidelines for teacher involvement to improve teacher education. The first section deals with how to begin, while the next two sections focus on what to find out from state agencies and what to do with state agencies. Section four contains information on participating in the National Council for Accreditation of Teacher Education, and section five discusses how to work with the Student NEA. Appended to this part is NEA Resolution 75-33 on teacher education. (RC)
Availability: National Education Association, 1201 Sixteenth Street, N.W., Washington, D.C. 20036 (NEA Stock No. 1376-x-00; No price quoted).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Accreditation (Institutions); Certification; Education Majors; Governance; Schools of Education; State Standards; Teacher Associations; Teacher Education; Teacher Influence; Teachers; National Council Accreditation Teacher Education -- National Council for Accreditation of Teacher Educ; Books